Cerebellar white matter pathways are associated with reading skills in children and adolescents. Issue 4 (12th December 2014) - Travis, Katherine E.; Leitner, Yael; Feldman, Heidi M.; Ben‐Shachar, Michal
Abstract: Reading is a critical life skill in the modern world. The neural basis of reading incorporates a distributed network of cortical areas and their white matter connections. The cerebellum has also been implicated in reading and reading disabilities. However, little is known about the contribution of cerebellar white matter pathways to major component skills of reading. We used diffusion magnetic resonance imaging (dMRI) with tractography to identify the cerebellar peduncles in a group of 9‐ to 17‐year‐old children and adolescents born full term (FT, n = 19) or preterm (PT, n = 26). In this cohort, no significant differences were found between fractional anisotropy (FA) measures of the peduncles in the PT and FT groups. FA of the cerebellar peduncles correlated significantly with measures of decoding and reading comprehension in the combined sample of FT and PT subjects. Correlations were negative in the superior and inferior cerebellar peduncles and positive in the middle cerebellar peduncle. Additional analyses revealed that FT and PT groups demonstrated similar patterns of reading associations within the left superior cerebellar peduncle, middle cerebellar peduncle, and left inferior cerebellar peduncle. Partial correlation analyses showed that distinct sub‐skills of reading were associated with FA in segments of different cerebellar peduncles. Overall, the present findings are the first to document associations of microstructure of the cerebellar peduncles and the component skills of reading. Hum Brain Mapp 36:1536–1553, 2015 . ©2014 Wiley Periodicals, Inc.